Economics of seawater desalination with innovative nuclear reactors and other energy sources: the EURODESAL project. (1st January 2004) - Nisan, S.; Volpi, L.
This paper summarises our recent investigations undertaken as part of the EURODESAL project on nuclear desalination, which were carried out by a consortium of four EU and one Canadian, Industrials and two leading EU R&D organisations. Major results of the project, in particular of its economic evaluation work package as discussed in this paper, are: 1. A coherent demonstration of the technical feasibility of nuclear desalination through the development of technical principles for the optimum cogeneration of electricity and water and by exploring the unique capabilities of the innovative nuclear reactors and desalination technologies; verification that the integrated system design does not adversely affect nuclear reactor safety. 2. The development of codes and methods for an objective assessment of the competitiveness and sustainability of proposed solutions through comparison, in European conditions, with fossil and renewable energy based solutions. The results obtained so far seem to be quite encouraging as regards the economical viability of nuclear desalination options. Thus, for example, specific desalination costs ($/m³ of desalted water) for nuclear systems such as the AP600 and the French PWR900 (reference base case), coupled to Multiple Effect Distillation (MED) or the Reverse Osmosis (RO) processes, are 30% to 60% lower than fossil energy based systems using pulverised coal and natural gas with combined cycle, at low discount rates and recommended fuel prices. Even in the most unfavourable scenarios for nuclear energy (discount rates = 10%, low fossil fuel prices) desalination costs with the nuclear options with the nuclear reactors are 7% to 15% lower, depending upon the desalination capacities. Furthermore, with the high performance coupling schemes developed by the EURODESAL partners, the specific desalination costs of nuclear systems are reduced by another 2% to 14%, even without system and design optimisation.